Once upon a Time in Loano, Purworejo: Mengasah Ketrampilan Berbicara dalam Bahasa Inggris dengan Storytelling - Zahroh, Adiba Qonita; Moehkardi, Rio Rini Diah; Hanidar, Sharifah; Alvanita, Alvanita (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
The Community Service Team of the English Studies Programme, Universitas Gadjah Mada, organised a programme at SMA 5 Purworejo, with the theme ‘Developing Speaking Skills through Storytelling.’ This programme was designed in response to a request from the teachers and the Principal of the SMAN 5 Purworejo, who considered that the students urgently need assistance in improving the students' English-speaking proficiency. This year's programme was conducted using a hybrid approach (online and offline). The programme focused on using folklore as a means to develop students’ speaking competence. As an initial step, the team provided the students with theoretical frameworks on language features, particularly those pertaining to English speaking skills. In the subsequent phase, the team assisted the students in applying the previously discussed language theories in two tutorial sessions. The students enthusiastically and actively participated in the tutoring sessions. They succeeded in applying the theories introduced to them. After that, the students were evaluated based on their performance. All evaluation components indicated that the students achieved above-average scores. === Tim Pengabdian kepada Masyarakat (PkM) Prodi Sastra Inggris Universitas Gadjah Mada telah menyelenggarakan program di SMA Negeri 5 Purworejo, dengan tema ‘Mengembangkan Keterampilan Berbicara Melalui Storytelling.’ Program ini dirancang untuk menjawab permintaan dari para guru dan kepala sekolah SMA Negeri 5 Purworejo, yang menilai bahwa siswa mereka sangat membutuhkan bantuan dalam meningkatkan kemampuan berbicara dalam Bahasa Inggris. Program tahun ini dilakukan dengan menggunakan pendekatan bauran (daring dan luring) yang berfokus pada penggunaan cerita rakyat sebagai sarana untuk mengembangkan kompetensi berbicara siswa. Sebagai langkah awal, tim membekali para siswa dengan kerangka teori tentang fitur kebahasaan, terutama yang berkaitan dengan keterampilan berbicara dalam Bahasa Inggris. Pada tahap selanjutnya, tim PkM mendampingi siswa dalam menerapkan teori-teori bahasa yang telah dibahas sebelumnya dalam dua sesi tutorial. Para siswa sangat antusias dan aktif berpartisipasi dalam sesi bimbingan. Mereka berhasil menerapkan teori-teori yang diperkenalkan kepada mereka. Setelah itu, siswa dievaluasi berdasarkan kinerja mereka. Semua komponen evaluasi menunjukkan bahwa siswa mencapai nilai di atas rata-rata.